2001
DOI: 10.1007/s004970100071
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural study on degeneration of tapetum in anther of snap bean ( Phaseolus vulgaris L.) under heat stress

Abstract: Pollen sterility was induced by heat stress applied about 10 days before flowering in the snap bean Phaseolus vulgaris L. Cytohistological changes in the tapetum during early development of the anther were studied to identify the tissues most sensitive to high temperature stress. The first distinct structural abnormalities were detected in the distribution pattern of the rough endoplasmic reticulum (RER) in the tapetum at the early microspore stage under high temperature conditions. Stacks of RER were frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
102
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 16 publications
5
102
0
2
Order By: Relevance
“…Anther indehiscence occurs in cowpea (Vigna unguiculata L.) due to heat stress (33/30˚C) and is associated with degeneration of tapetal layer (Ahmed et al 1992). The degeneration of tapetum cells was also found in common bean (Phaseolus vulgaris L.) at 33/29˚C (Suzuki et al 2001), resulting in premature pollen development within the anther during early development. High temperature (33/27˚C) before anthesis can also cause anther indehiscence and pollen sterility in common beans (Gross and Kigel, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Anther indehiscence occurs in cowpea (Vigna unguiculata L.) due to heat stress (33/30˚C) and is associated with degeneration of tapetal layer (Ahmed et al 1992). The degeneration of tapetum cells was also found in common bean (Phaseolus vulgaris L.) at 33/29˚C (Suzuki et al 2001), resulting in premature pollen development within the anther during early development. High temperature (33/27˚C) before anthesis can also cause anther indehiscence and pollen sterility in common beans (Gross and Kigel, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…During this process, the young microspore stage has been reported to be the most sensitive to temperature changes. In the tapetum, the innermost cell layer of the anther is known to be the most sensitive cell layer to environmental stress during the young microspore stage (Suzuki et al, 2001). Additionally, some researchers have reported that the flowering stage and the young microspore stage of rice were most sensitive to HT stress, showing poor anther dehiscence during flowering and disrupted tapetum functions during young microspore development (Sato et al, 2002;Endo et al, 2009).…”
mentioning
confidence: 99%
“…Cultivar Haibushi has been selected for its heat tolerance (Nakano et al, 1997) and produces higher pod yield and maintains higher leaf water content than Kentucky Wonder after exposure to high temperature (Omae et al, 2004(Omae et al, , 2005bKumar et al, 2005). The pod yield is also directly affected by high temperature due to the lack of pollination, and increased senescence and abscission of flowers and young pods (Suzuki et al, 2001a). Cultivars Haibushi and Kentucky Wonder did not differ in pollen fertility but the former showed higher pod setting and retention than the latter (Omae et al, 2005a).…”
mentioning
confidence: 99%